2014
DOI: 10.1002/art.38861
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Body Mass Index, Fat Mass, Muscle Mass, and Musculoskeletal Pain in Community Residents

Abstract: Objective. To evaluate the relationships between fat mass, muscle mass, fat:muscle mass ratio, metabolic syndrome, and musculoskeletal pain in community residents.Methods. In the Korean Health and Genome Study, 1,530 participants (mean ؎ SD age 60.8 ؎ 8.60 years) completed pain questionnaires and underwent dual x-ray absorptiometry to calculate body composition. Pain was categorized according to the number of pain regions, such that widespread pain, defined as pain above the waist, below the waist, on both sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 51 publications
6
55
0
1
Order By: Relevance
“…The present study also indicated that there was no significant relation between pain intensity and body mass index. Consistent with our results a Korean study claimed that pain was more prevalent among subjects with metabolic syndrome whether their BMI was high or normal (31) . On the other hand, an Australian study reported that obese individuals with knee OA reported more pain and worsened function (2) .…”
Section: Discussionsupporting
confidence: 93%
“…The present study also indicated that there was no significant relation between pain intensity and body mass index. Consistent with our results a Korean study claimed that pain was more prevalent among subjects with metabolic syndrome whether their BMI was high or normal (31) . On the other hand, an Australian study reported that obese individuals with knee OA reported more pain and worsened function (2) .…”
Section: Discussionsupporting
confidence: 93%
“…Alcohol itself can cause anti-nociceptive effects. 31 Additionally, pain has been associated with adiposity 32 , and BMI was significantly higher among members of our cohort with HCV and NASH than alcohol. BMI fell out of the models because it was not related to pain in this group, but this factor should be further explored in larger studies.…”
Section: Discussionmentioning
confidence: 78%
“…This association was confirmed in a recent Korean study, which showed that an increase in adipose tissue mass and adipose tissue mass/muscle ratio was associated with musculoskeletal pain among women. 74 A cohort study of 385 female Finnish kitchen workers, evaluated repeatedly at 3-month intervals over 2 years, 75 documented an increased prevalence of widespread pain (OR, 2.8) associated with obesity. Conversely, not being obese was associated with a reduced prevalence of widespread pain (OR, 3.7), defined in this study as hurting at 3 or more of 7 sites.…”
Section: Chronic Widespread Pain and Fibromyalgiamentioning
confidence: 99%